Value Stream Mapping (VSM) in a manufacture-to-order small and medium enterprise - Stamm, M; Neitzert, T (JOMSA, 2008)
This paper discusses the Lean methodology of Value Stream Mapping (VSM) in a manufacture-to order (MTO) environment. Within a case study of a mold making company the method is applied and improved. The purpose of VSM is to initialise the Lean transformation and to understand the value streams of a company as a basis for further improvements. The paper explores the current literature about VSM and also discusses the specific characteristics of a MTO environment and its limitations regarding the application of the current VSM methodology. Based on this an adapted VSM procedure with a special focus on MTO small and medium enterprises is presented. The first adapted VSM analysis provided valuable insights into the material flow for the management team. Therefore it was decided to use this method in a modified way as a “Value Stream Monitoring” tool which observes the impacts of all Lean implementation activities.
Keywords: Value Stream Mapping; Lean production; SME